Essential texts on human rights for the police : a compilation of international instruments - Crawshaw, Ralph; Holmström, Leif (Raoul Wallenberg Institute professional guides to human rights ;, 2008)
Human rights law protects the rights and freedoms of individuals and groups within societies. Police officials are uniquely placed to ensure respect for, and secure protection of, those rights and freedoms. Those who exercise power on behalf of the people they serve need to be aware of the human rights standards they are required to meet, and the best practice in their fields of activity.